Patrones y clientes : El empleo municipal en el Buenos Aires de los primeros gobiernos radicales (1916-1930) - Horowitz, J.
tbls.
pp. 569-596
Keywords: Argentina; Empleo; Buenos Aires (argentina); Empleados; Gobierno Municipal; Etapa Radical; Siglo XX